Supranational rules, national discretion: Increasing versus inflating regulatory bank capital? - Reint Gropp; Thomas Mosk; Steven Ongena; Ines Simac; Carlo Wix (Leibniz Institute for Financial Research SAFE, 2020)
We study how higher capital requirements introduced at the supranational level affect the regulatory capital of banks across countries. Using the 2011 EBA capital exercise as a quasi-natural experiment, we find that treated banks exploit discretion in the calculation of regulatory capital to inflate their capital ratios without a commensurate increase in their book equity and without a reduction in bank risk. Regulatory capital inflation is more pronounced in countries where credit supply is expected to tighten, suggesting that national authorities forbear their domestic banks to meet supranational requirements, with a focus on short-term economic considerations.
Keywords: 330